2000
DOI: 10.1093/gerona/55.9.m508
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of Functional Recovery 1 Year After Hip Fracture: Typical Patient Profiles Through Cluster Analysis

Abstract: Subjects of two clusters could walk without difficulty and were functionally independent prior to their hip fracture. One year later, however, mobility and functioning were only fully recovered by the members of one cluster. The majority of predictors were of less favorable prognostic value for the members of the second cluster. The other two clusters regrouped patients with impaired prefracture mobility that were either unaltered or even aggravated 1 year later. CONCLUSIONS. Cluster analysis identified typica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0
4

Year Published

2002
2002
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 13 publications
3
40
0
4
Order By: Relevance
“…Although the majority of the patients undergo surgical treatment, the proportion of those not completely recuperating to their previous levels of independence remains high. Many studies have identified specific pre-operative indicators of long-term outcome based on background demographic, social, and health variables, as well as living conditions and functional varlables such as pre-morbid state and activities of daily living (2)(3)(4)(5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Although the majority of the patients undergo surgical treatment, the proportion of those not completely recuperating to their previous levels of independence remains high. Many studies have identified specific pre-operative indicators of long-term outcome based on background demographic, social, and health variables, as well as living conditions and functional varlables such as pre-morbid state and activities of daily living (2)(3)(4)(5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Oscilan, según los diferentes estudios desde el 20% al 40% al alta hospitalaria (48,62,77), entre el 25 y el 55% durante los primeros meses tras la fractura (8,49,57,78,79), el 30 al 50% a los 12 meses (8,31,36,56,78,(80)(81)(82)(83)(84)(85), 72% a lo largo de los dos primeros años tras la fractura (86) o 55% a los 3 años (87). Otros estudios con criterios de selección más estrictos de los pacientes ancianos con fractura dan unas cifras de recuperación cercanas al 90% desde los primeros meses tras la fractura (55,58,88).…”
Section: Tasa De Recuperaciónunclassified
“…Así pues, si en lugar de comparar el resultado con la capacidad de deambulación tras la fractura, se compara con el nivel previo de los sujetos estudiados las tasas de recuperación son del 20 al 36% a los 3 ó 4 meses (55,65,89), 33 al 75% a los seis meses (47,90), y del 40 al 80% a los 12 meses (34,53,55,56,65,71,73,89,91,92). Por lo general, las series publicadas muestran que el uso de ayudas instrumentales para la deambulación aumenta con respecto a la situación previa a la fractura (58,81,93).…”
Section: Tasa De Recuperaciónunclassified
See 2 more Smart Citations